Modernization of Accounting Practices for MSMEs in Developing Countries: Systematic Literature Review - Desak Nyoman Lia Lestari; Inten Meutia; Rela Sari (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the economies of developing countries, yet they continue to face significant challenges in modernizing accounting practices. This study aims to identify trends, challenges, and strategies in promoting the modernization of MSME accounting through a Systematic Literature Review (SLR) approach. The literature analyzed comprises 30 selected articles out of 346 publications published between 2018 and 2025, sourced from leading academic databases such as Emerald Insight, DOAJ, and ResearchGate, and indexed in reputable databases including Scopus, Copernicus, Sinta, or published in international scientific conference proceedings. The review findings indicate that institutional pressures, such as government regulations and market expectations, greatly influence the adoption of modern accounting practices, alongside internal factors such as financial literacy and business leadership. Accounting technologies, including Accounting Information Systems (AIS), e-payment, and fintech, have proven to enhance financial reporting efficiency, yet are hindered by low digital literacy and infrastructural limitations. This study emphasizes that MSME accounting modernization requires a contextual approach that considers social, cultural, technological, and institutional aspects unique to each country. These findings may serve as a basis for formulating policies to support increased transparency, accountability, and sustainability of MSMEs in developing countries.